Design and Construction of a Website-Based Water Apple Ordering and Management System - Karimah; Alif Catur Murti; Ratih Nindyasari (Komunitas Dosen Indonesia, 2025)
This study aims to design and implement a website-based ordering and management system specifically for water apple commodities in Betokan Village, Demak. Farmers in this area previously relied on manual stock and transaction recording, which led to frequent issues such as data inaccuracy, difficulties in inventory tracking, and inefficiencies in sales operations. To address these challenges, a digital system was developed using the Waterfall method, comprising five stages: requirements analysis, system design, implementation, testing, and maintenance. The platform was built using the PHP programming language with the Laravel framework and a MySQL database. The system includes key features such as real-time stock updates, online ordering, transaction recording, and automated report generation. Evaluation of the system was conducted using black-box testing on eight core functions, of which 87.5% passed as expected. Post-implementation results showed a 60% reduction in inventory-related errors and a notable decrease in administrative workload. The system was also piloted with a sample group of local users, and feedback indicated increased efficiency in stock monitoring and transaction processing. This research contributes significantly to the digital transformation of local agricultural communities by offering a practical, scalable solution that improves business operations and customer service. Moreover, it enhances the ability of rural farmers to enter the digital market ecosystem and expand their market reach. The system demonstrates how localized digital tools can bridge gaps in rural agribusiness, increase productivity, and promote economic resilience through technology adoption.